In Vitro Determination of Antileshmanial Activities of Benzimidazolium Derivatives on L. major Promastigotes and Amastigotes - Kelleci, Kubra; Golebatmaz, Eda (SPRINGER INT PUBL AG, 2023)
Purpose Leishmaniasis is a serious public health problem infecting millions of people worldwide. An effective and reliable treatment method to be used in the treatment of the disease has not been developed yet. Methods In this article, the anti-leishmanial activities of two benzimidazolium derivatives (B.A and B.B) against Leishmania major promastigotes and amastigotes, which are known to cause cutaneous leishmaniasis, were investigated for the first time. The immunostimulatory activity of the developed formulations was determined using the J774 murine macrophage cell line. Results B.A and B.B compounds were found to have a much higher cytotoxic effect than Amphotericin B (IC50 value 0.75 mu M +/- 0.03), which is used as the reference drug. The IC50 value was determined as 2.02 mu M +/- 0.52 for B.A and 1.83 mu M +/- 0.71 for B.B in Leishmania promastigotes. In addition, IC50 values of B. A and B.B Leishmania amastigotes were found to be 1.01 mu M and 0.67 mu M, respectively. It was found that B.B was 81.12 times more selective than Amphotericin B and showed the highest selectivity against L. major promastigotes (359.09) and amastigotes (980.80). Considering the selectivity indices (SI) of B.A and B.B, both compounds tested are more promising than Amphotericin B. Conclusion The results showed that benzimidazolium derivatives have anti-leishmanial potential against L. major, which is the causative agent of cutaneous leishmaniasis. Thus, we can say that the obtained results will help the development of effective and safe antileishmanial drug formulations against cutaneous leishmaniasis.
Keywords: Benzimidazolium; Leishmania major; Cutaneous Leishmaniasis; Parasitology; Veterinary Sciences; Zoology